Glucose Driven Changes in Beta Cell Identity Are Important for Function and Possibly Autoimmune Vulnerability during the Progression of Type 1 Diabetes - Weir, Gordon C.; Bonner-Weir, Susan (Frontiers in Genetics, 2017)
This commentary explores the hypothesis that when autoimmunity leads to a fall of beta cell mass during the progression of type 1 diabetes (T1D), rising glucose levels cause major changes in beta cell identity. This then leads to profound changes in secretory function and less well-understood changes in beta cell susceptibility to autoimmune destruction, which may influence of rate of progression of beta cell killing.